Assessment of esophageal dysfunction and symptoms during and after a standardized test meal: development and clinical validation of a new methodology utilizing high‐resolution manometry. Issue 2 (18th November 2013) - Sweis, R.; Anggiansah, A.; Wong, T.; Brady, G.; Fox, M.
Abstract Background In the absence of major dysmotility, esophageal manometry with water swallows rarely explains the causes of esophageal symptoms and disease. This methodology development study assessed esophageal function and symptoms during a test meal in patients with reflux symptoms and asymptomatic controls. The impact of this approach on manometric diagnosis and clinical outcome was reviewed. Methods 18 patients with reflux symptoms and 10 healthy volunteers underwent high resolution manometry (HRM) with 5 mL water swallows, 200 mL water drink, and standardized solid test meal followed by 10 min postprandial observation. The number of symptoms associated with esophageal dysfunction (SAD) divided by total symptoms (dysfunction symptom index [D‐SI]) was calculated. Ambulatory reflux pH‐monitoring was performed. Final diagnosis and clinical outcome were documented at 2 years. Key Results Meal intake took longer in patients than controls (552 vs 339 s) and this was associated with a higher number of ineffective swallows in this group (51% vs 28%; p < 0.001). No swallowing problems occurred with water swallows but 12/18 (66%) patients had SAD during either the meal or postprandial observations with D‐SI >50% in 9/12 (75%). Compared with water swallows, manometric classification was altered in 12/18 (67%) and clinical diagnosis was altered in 7/18 (39%) patients due to test meal observations. Conclusions & Inferences A novel methodology for the detection of symptomatic dysmotility during a test meal and postprandial observation is presented. This technique increased the diagnostic yield of esophageal dysfunction in patients presenting with reflux symptoms. Long‐term follow‐up indicated that these observations can guide effective clinical management.